Development of Portable Self-Powered Disinfection Systems Based on Triboelectric and Thermoelectric Effects. (21st March 2018) - Chiu, Che-Min; Lin, Yu-Jhen; Lin, Zong-Hong
Abstract : Pathogenic bacteria that give rise to infection remain a major health concern over the past several decades. In this study, we proposed a concept of self-powered active disinfection system for wearing clothes. The system was mainly composed of a power generator to convert either biomechanical energy or thermal energy into electricity, and conductive fabrics as electrodes to build a wearable disinfection cell. Based on different power sources, we develop two types of self-powered antibacterial fabrics. For the use of biomechanical energy as a power supply, we applied triboelectric nanogenerator (TENG) to effectively harvest energy from human motions; for converting thermal energy into electricity, a Ag2 Te thermoelectric nanogenerator was used. The working principle of the system was based on hybrid effects of H2 O2 production, showing good disinfection effects toward Gram-negative Escherichia coli (E. coli). To conclude, the self-powered active disinfection system behaves as an ideal candidate to combat with pathogenic bacteria in biomedical and environmental applications.